Impact of the Generation and Activation of Sea Salt Aerosols on the Evolution of Tropical Cyclone Dumile. Issue 16 (24th August 2018) - Hoarau, T.; Barthe, C.; Tulet, P.; Claeys, M.; Pinty, J.‐P.; Bousquet, O.; Delanoë, J.; Vié, B.
Abstract: An original coupling between an aerosol scheme and a two‐moment microphysics scheme has been developed in the cloud‐resolving model Meso‐NH to fully represent the aerosol‐microphysics‐dynamics interactions in tropical cyclones. A first evaluation of this coupling is performed through the simulation of tropical cyclone Dumile (2013) in the South‐West Indian Ocean. MACC (Monitoring Atmospheric Composition and Climate project) analysis and CALIPSO (Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations) data agree about the predominance of sea salt aerosols. The aerosol‐microphysics coupled system reproduces the track and intensity of Dumile well, with a transition from a monsoon depression to a tropical cyclone, and produces ice water contents that compare well with the DARDAR (raDAR/liDAR) product. Using a one‐moment microphysics scheme produces a more intense and symmetric system tracking too far to the west. In the aerosol‐microphysics coupled simulation, sea salt aerosols, the main source of cloud condensation nuclei (CCN), are preferentially produced in regions with high winds and waves, which reinforce convective asymmetries compared to the simulation with the one‐moment scheme. Using a two‐moment microphysics scheme without explicit sea salt emission led to a dramatic weakening of Dumile after 24 hr of simulation due to the consumption and scavenging of all interstitial CCN in the inner core. The importance of explicitly taking account of sea salt aerosol emissions associated with high winds and waves in tropical cyclones is a critical point for simulating long‐lasting systems that need to generate their own CCN. Key Points: The coupling between an aerosol scheme and a two‐moment microphysics scheme is done in the cloud‐resolving model Meso‐NH Explicitly taking account of sea salt aerosol emissions associated with high winds and waves in tropical cyclones is essential